THE INTERNATIONAL COALITION IN AFGHANISTAN: CERTAIN ASPECTS OF STRATEGY - AKMALOV, Shaislam (CENTRAL ASIA AND THE CAUCASUS, 2011)
Settlement of the situation relating to Afghanistan has been and remains one of the most urgent tasks of world politics. It is becoming increasingly clear that pacification calls for nonmilitary methods: the counterterrorist coalition has failed. With each passing day, the war is pushing the people of Afghanistan deeper into an abyss and making any solution next to impossible.1 The huge efforts of the international community and the coalition forces have done nothing to improve the situation; it is going from bad to worse: radical forces are regaining their positions to add an edge to the already high tension, while the militants are stepping up their terrorist activities. The trouble broiling in Pakistan is having a negative effect on everything that is going on in Afghanistan; Hamid Karzai’s corrupt and incompetent government has merely added to the obvious impotence of power in Kabul.2 The situation in the country is extremely unstable despite the fact that coalition forces have been stationed in the country for 9 years now. The destructive forces have stepped up their activity in the country’s north (the Balkh and Kunduz provinces), as well as in other parts of the country that were recently considered “safe,” which is arousing particular concern. It should be said that the Taliban has mastered fundamentally new tactics: today suicide bombers are its inalienable part. The scores of international conferences and meetings expected to solve the Afghan problem have proven useless; there is no more or less specific plan of action either. This means that the international community has learned to live with the problem.